Pengenalan Aplikasi Ovo Untuk Umkm Solusi Pembayaran Laundry Bunda Erma - Candriani, Afri; Efendi, Bahman; Novita, Dhea; Permana, Dani (Universitas Dehasen Bengkulu, 2025)
Transaction reporting and financial management systems play a vital role in ensuring the efficiency and sustainability of businesses, both small and large. The development of technology has brought major changes to corporate procedures, including the transformation of MSMEs from manual paper-based records to a more modern digital system. One innovative solution is the use of digital wallet applications such as OVO, which is popular in Indonesia. OVO allows its users to conduct various financial transactions online, including cashless payments, money transfers and bill payments. In this context, payment is the process of transferring value from a consumer to another party, whether for the purchase of goods or services, payment of bills, or transfer of funds. With OVO, the payment process becomes faster, more practical and secure, helping MSMEs adapt to modern technology and improve their operational efficiency. In addition, the app also makes it easier for consumers to keep up with the trend of digital transactions, creating comfort and convenience in their daily lives and business activities. The adoption of payment technology like this supports the digital transformation of MSMEs and encourages more inclusive economic growth.